Welfare Improvement Strategies Kub Chicken Farmers in Central Java Province - Iif Syarifah; Sitti Nurani Sirajuddin; Syahdar.Baba; Mukhamad Najib (Migration Letters, 2023)
The sustainability of the KUB chicken business, the increase in farmers’ income and the fulfillment of farmers’ living needs are the parameters of farmers’ welfare. The purpose of this study was to formulate strategies to improve the welfare of farmers in the KUB chicken business in supporting sustainable livestock development. This research was conducted in March 2023 using a questionnaire with a sampling of 10 respondents consisting of farmers, researchers, policy analysts and government officials in Central Java. The method used to determine strategic steps in achieving farmer welfare parameters is AHP (Analytical Hierarchy Process). AHP is a method used to help solve complex qualitative problems using quantitative calculations. Through the process of expressing problems in an organized framework, it is possible to carry out the decision-making process effectively. The results of the research can determine the priority steps that need to be taken, starting from KUR cooperation (ideal: 1.0000 normal: 0.2404 and total: 0.0801), increasing production capacity (ideal: 0.8551, normal: 0.2056 and total: 0.0685), institutional strengthening (ideal: 0.7900, normal: 0.1899 and total: 0.0633), empowerment of millennial breeders (ideal: 0.7900, normal: 0.1874 and total: 0.0625) and the last (ideal: 0.7347, normal: 0.1767 and total: 0.0589) is increasing breeder knowledge.